Wavelength-shifting performance of polyethylene naphthalate films in a liquid argon environment. (12th July 2021) - Abraham, Y.; Asaadi, J.; Basque, V.; Castiglioni, W.; Dorrill, R.; Febbraro, M.; Hackett, B.; Kelsey, J.; Littlejohn, B.R.; Parmaksiz, I.; Rooks, M.; Szelc, A.M.
Abstract: Liquid argon is commonly used as a detector medium for neutrino physics and dark matter experiments in part due to its copious scintillation light production in response to its excitation and ionization by charged particle interactions. As argon scintillation appears in the vacuum ultraviolet (VUV) regime and is difficult to detect, wavelength-shifting materials are typically used to convert VUV light to visible wavelengths more easily detectable by conventional means. In this work, we examine the wavelength-shifting and optical properties of poly(ethylene naphthalate) (PEN), a recently proposed alternative to tetraphenyl butadiene (TPB), the most widely-used wavelength-shifter in argon-based experiments. In a custom cryostat system with well-demonstrated geometric and response stability, we use 128 nm argon scintillation light to examine various PEN-including reflective samples' light-producing capabilities, and study the stability of PEN when immersed in liquid argon. The best-performing PEN-including test reflector was found to produce 34% as much visible light as a TPB-including reference sample, with widely varying levels of light production between different PEN-including test reflectors. Plausible origins for these variations, including differences in optical properties and molecular orientation, are then identified using additional measurements. Unlike TPB-coated samples, PEN-coated samples did not produce long-timescale light collection increases associated with solvation or suspension of wavelength-shifting material in bulk liquid argon.